Building agreement using emotions as you negotiate - Fisher, Roger 1922-; Shapiro, Daniel 1971- (Random House Business Books, 2007)
Whether you're negotiating with an angry boss or a difficult colleague - or, indeed, a stubborn teenager - you can learn to use your emotions to help you achieve the result you want. This text shows you how to control the five 'core concerns' that motivate people.